Approximate Solutions to a Degenerate Diffusion Equation with Absorption and Production: A Sharp Front Approach - Jordan Hristov (Applied Sciences)
Approximate analytical solutions to a degenerate reaction–diffusion model with power-law absorption (source) and production (sink) terms have been developed. The integral-balance method applied to a preliminary transformed model and by a direct integration approach has provided physically reasonable results. The model equation scaling has revealed the characteristic length and times scales and the Fourier number as the controlling dimensionless group.